Participation in eHealth Communication Interventions Among Patients Undergoing Hemodialysis: Scoping Review - Anne Deinboll; Cathrine Fredriksen Moe; Mette Spliid Ludvigsen (JMIR Publications, 2024)
BackgroundeHealth communication interventions have been shown to offer individuals with chronic kidney disease the opportunity to embrace dialysis therapies with greater confidence, the potential to obtain better clinical outcomes, and an increased quality of life. eHealth is an emerging field that offers diverse, flexible designs and delivery options. However, existing evidence on eHealth communication among patients undergoing hemodialysis is sparse and scattered and lacks systematization. ObjectiveThis scoping review aims to identify and map the current evidence on patient participation in eHealth communication interventions. We aimed to map the associations between interventions and electronic health records, the participative role of individuals living with chronic kidney disease and undergoing hemodialysis, and the barriers to and facilitators of patient involvement in eHealth communication with health care professionals. MethodsThis study used the Joanna Briggs Institute methodology for conducting a scoping review. Studies eligible for inclusion were those that included adult patients (aged >18 y) undergoing all types of hemodialysis, including prescheduled in-center hemodialysis and conventional home-based hemodialysis. Systematic searches were completed in Ovid MEDLINE, Ovid Embase, EBSCOhost CINAHL with Full Text, Scopus, and ProQuest Dissertations and Theses. Extracted data from the included studies were presented in figures and tables along with descriptions that responded to the research questions. This review was reported according to the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines. ResultsIn total, 9 peer-reviewed studies were included. The main result was a low participative patient role and a vaguely described link to electronic health records. The key participative facilitators were availability of and access to the intervention; security, trust, and confidence; patient knowledge of their health situation and use of self-care; and patient preparedness for an uncertain future health situation and the ability to relate to family and friends about it. The key participative barriers were lack of availability of and access to information, mistrust and lack of safety, lack of knowledge of health situation and self-care, and relational issues. All barriers and facilitators were related to health literacy. ConclusionsThis scoping review summarizes 4 specific and 3 nonspecific eHealth communication interventions developed and evaluated in various studies involving patients receiving hemodialysis. A knowledge gap exists between low levels of patient participation in eHealth communication and patients' limited access to electronic health records. eHealth communication interventions should implement patient participation and focus on the fact that different modalities of eHealth communication can complement face-to-face communication. International Registered Report Identifier (IRRID)RR2-10.2196/38615